Inflammatory Caspases Drive Pyroptosis in Acute Lung Injury - Liu, Bohao; He, Ruyuan; Zhang, Lin; Hao, Bo; Jiang, Wenyang; Wang, Wei; Geng, Qing (Frontiers in Pharmacology, 2021)
Acute lung injury (ALI), a critical respiratory disorder that causes diffuse alveolar injury leads to high mortality rates with no effective treatment. ALI is characterized by varying degrees of ventilation/perfusion mismatch, severe hypoxemia, and poor pulmonary compliance. The diffuse injury to cells is one of most important pathological characteristics of ALI. Pyroptosis is a form of programmed cell death distinguished from apoptosis induced by inflammatory caspases, which can release inflammatory cytokines to clear cells infected by pathogens and promote monocytes to reassemble at the site of injury. And pyroptosis not only promotes inflammation in certain cell types, but also regulates many downstream pathways to perform different functions. There is increasing evidence that pyroptosis and its related inflammatory caspases play an important role in the development of acute lung injury. The main modes of activation of pyroptosis is not consistent among different types of cells in lung tissue. Meanwhile, inhibition of inflammasome, the key to initiating pyroptosis is currently the main way to treat acute lung injury. The review summarizes the relationship among inflammatory caspases, pyroptosis and acute lung injury and provides general directions and strategies to conduct further research.